Impact of obesity on restoration of sagittal balance and clinical efficacy after posterior lumbar interbody fusion. (November 2019) - Zhang, Yijian; Zhang, Junxin; Liu, Hao; Shao, Yijie; He, Fan; Chen, Angela; Yang, Huilin; Pi, Bin
Highlights: Obesity can significantly increase the risk of blood loss and operation duration in posterior lumbar interbody fusion (PLIF). Obesity had negative impact on restoration of sagittal balance and clinical outcomes. There was significant correlation between BMI and change of pelvic tilt (PT) and lumbar lordosis (LL). PT played a critical role in correction of sagittal balance and improvement of ODI scores. Abstract: To investigate the impact of obesity on the restoration of sagittal balance after posterior lumbar interbody fusion (PLIF). To examine the correlation between obesity and sagittal balance and their influence on clinical efficacy. A total of 183 patients who underwent PLIF for degenerative lumbar diseases between Jan 2015 and Dec 2015 were enrolled in this study. Based on their BMI, patients were divided into three groups: normal weight group (Group A), overweight group (Group B), and obesity group (Group C). Demographic data, intraoperative data, sagittal balance parameters, and clinical function scores were compared between each group. Correlation analysis was conducted between the BMI scores and each sagittal balance parameter. Multiple linear regression was used to assess the impact of each variable on clinical outcomes. All patients finished an average of 22.3 months follow-up. Group C had significantly higher blood loss and longer operations than Group A. SL and PT improved significantly in Group A while did not change in Group C. Compared with Group C, Group postoperative pelvic tilt (PT) was better restored in Group A. BMI was significantly correlated with change of lumbar lordosis (LL) and PT. Multiple linear regression analysis indicated that BMI and change of PT had a great influence on ODI improvement. Obesity may hinder the correction of sagittal balance and improvement of clinical efficacy in patients who undergo PLIF. Restoration of PT should be paid more attention to during surgery, as it may be associated with satisfactory clinical outcomes especially for obesity.